The Influence of Financial Aspects, Human Resource (HR) Competence, and Product Innovation on the Performance of Micro, Small, and Medium Enterprises (MSMEs) in Menteng District - Melisa Riswania; Mohamad Lutfi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
MSMEs play a strategic role in Indonesia and are crucial for the economy, employment, job creation, and poverty reduction. In 2023, MSMEs contributed 61.07 percent to the national GDP and employed 97 percent of the Indonesian workforce. As competition increases, it is crucial to understand the factors that can help MSMEs perform more effectively. Good financial health combined with strong human resource capabilities supports better innovation capabilities, which in turn improves the level and quality of not only competitiveness but also overall business performance. The research conducted in this paper aims to investigate the influence of financial aspects, human resource competencies, and product innovation on business performance, both partially and jointly. The research method used is quantitative, employing a survey method. Data were collected through a questionnaire using a Likert Scale, which was distributed to 100 registered MSME owners in the Menteng area. The sampling method used a purposive sampling method. The data analysis method utilized SPSS to examine the relationship and influence between the variables of financial aspects, human resource competencies, and product innovation on business performance. The results of the study indicate that the financial aspect variable has a significant positive influence on business performance (0.000 at a 5% significance level). The HR competency variable also has a significant positive influence (0.000 at a 5% significance level), as does the product variable (0.023 at a 5% significance level). The simultaneous test also shows that the financial aspect variable, HR competency, and product innovation all have a significant positive influence (0.000 at a 5% significance level). Therefore, by improving these three elements simultaneously, integrated financial management, HR competency development, and product innovation can provide business actors with an effective means to increase performance competitiveness.